Flood Risk Management Through Digital Transformation in Connection with Smart Urban Development Management: A Case of Lao Cai City of Vietnam - Ngo, Hung V.; Do, Hau (International Journal of Sustainable Construction Engineering and Technology, 2024)
This paper develops an approach of smart city and smart urban governance by providing ideas for using digital transformation as a tool for flood risk management and how they are translated into practice. Smart tools can only be applied if there are sufficient data provided. Therefore, real-time data and updated data collection are vital. The information is important but the more important part is the exchange data procedure or information sharing. Co-operation and participation among stakeholders in providing and sharing information can create a foundation for a smart city. The case study of Lao Cai city of Vietnam shows that digital transformation and data sharing among departments act as decision-support sources for leaders while promoting the interests of the community and professionals in urban development direction. The study suggests that instead of waiting for a synchronous system to be built in a unified standard, all levels of government in every sector need to share their data for step-by-step smarter management.